The Global Causes of Road Traffic Accidents And Impact on The Economy - Anvarovna, Matkarimova Dilfuza; Parhah, Siti; Kholbaev, Bakhrom (The International Journal of Business Review (The Jobs Review), 2023)
The article "Global causes of road traffic accidents and impact on the economy" highlights the critical issue of road safety and its global impact. it discusses the rising number of road accidents and deaths, and the economic and social costs associated with them. The article emphasizes the need for a comprehensive approach to road safety, including infrastructure improvements, education and awareness programs, and strict enforcement of traffic laws. It also highlights the importance of collaborative efforts between governments, civil society, and the private sector in addressing this issue. The article concludes by